Insight into the Mechanism of Action and Peptide‐Membrane Interactions of Aib‐Rich Peptides: Multitechnique Experimental and Theoretical Analysis. (24th February 2021) - Lizio, Maria Giovanna; Campana, Mario; De Poli, Matteo; Jefferies, Damien F.; Cullen, William; Andrushchenko, Valery; Chmel, Nikola P.; Bouř, Petr; Khalid, Syma; Clayden, Jonathan; Blanch, Ewan; Rodger, Alison; et al.
Abstract: The increase in resistant bacterial strains necessitates the identification of new antimicrobial molecules. Antimicrobial peptides (AMPs) are an attractive option because of evidence that bacteria cannot easily develop resistance to AMPs. The peptaibols, a class of naturally occurring AMPs, have shown particular promise as antimicrobial drugs, but their development has been hindered by their mechanism of action not being clearly understood. To explore how peptaibols might interact with membranes, circular dichroism, vibrational circular dichroism, linear dichroism, Raman spectroscopy, Raman optical activity, neutron reflectivity and molecular dynamics simulations have been used to study a small library of peptaibol mimics, the Aib‐rich peptides. All the peptides studied quickly partitioned and oriented in membranes, and we found evidence of chiral interactions between the phospholipids and membrane‐embedded peptides. The protocols presented in this paper open new ground by showing how chiro‐optical spectroscopies can throw light on the mechanism of action of AMPs. Abstract : Sit up or lie down : Linear dichroism, circular dichroism and Raman spectroscopy, neutron reflectivity and molecular dynamics simulations have been used to explore how mimics of peptaibol antibiotics (Aib foldamers) interact with membranes. These studies revealed all peptides partitioned well into the bilayers, with orientation dependent upon peptide length, as well as chiral interactions between peptides and the phospholipids.